Effects of Health Expenditure on Life Expectancy in Nepal - Paudel, Omkar; Kumar, Nand Kishor; Acharya, Pradeep; KC, Abhiyan (Dhaulagiri Journal of Contemporary Issues, 2025)
This study examines the long-run impact of health expenditure on life expectancy in Nepal, a low-income country with unique socio-economic and public health challenges. Using annual time-series data from 2001 to 2021, the research employs the Dynamic Ordinary Least Squares (DOLS) method to estimate long-term elasticities and conducts Granger causality tests to explore predictive relationships. The analysis controls for GDP per capita, educational attainment, and access to safe drinking water. The findings reveal that a 1% increase in health expenditure per capita is associated with a 0.031% rise in life expectancy (p = 0.0111), while educational attainment exerts a stronger effect, with a 0.349% increase (p = 0.0018). Surprisingly, GDP per capita shows a negative coefficient (-0.255%, p = 0.006), possibly reflecting income inequality and urban-rural disparities in health access. Safe water access also has a modest positive effect (0.024%, p = 0.018). Granger causality tests indicate that life expectancy significantly predicts future gains in GDP and education, highlighting a feedback loop between health and development. The Wald test confirms the joint significance of all explanatory variables (p < 0.01), and diagnostic tests validate the model's robustness. These results underscore the importance of targeted health and education investments and call for inclusive policies to ensure equitable health outcomes across Nepal.